Investigation of the influence of different parameters on chatter arising during metal cutting process - Amin, A. K. M. Nurul; Khaled, Khalil (1999)
Stiffness of tool bit holder, cutting variables and tool geometry are the most important elements which determine machine tool chattel, the stiffness of tool bit holder playing the major role. During metal cutting operation high frequency chatter maintains a definite relationship with stiffness of tool bit holder, cutting variables and tool geometry. High frequency chatter can be identified by the poorer surface finish and whirling sound during metal cutting operation. At critical range of cutting speed, metal cutting process is accompanied with chatter, when either the job and spindle or the tool bit holder vibrate with their natural frequencies. Frequency level and amplitude of such chatter, depend mainly on the stiffness of tool bit holder. It has been established in the present work that chatter can be controlled by controlling stiffness of tool bit holder and cutting variables. The results of the present study may facilitate the selection of appropriate tool bit holders for specific type of metal cutting operation.